复合纳米生物催化剂Fe3 O4-ZIF-8@ET 2.0的 制备及表征Preparation of composite nano-biocatalyst Fe3O4-ZIF-8@ET 2.0 and its characterization - 李攀登，贺雷雨，孙丽慧 LI Pandeng， HE Leiyu， SUN Lihui (Zhongguo youzhi)
为提高脂肪酶Eversa Transform 2.0稳定性和利用率，采用共沉淀法将磁性纳米粒子Fe3O4与金属有机框架材料ZIF-8耦合，并使脂肪酶Eversa Transform 2.0固定于复合材料上，制备复合纳米生物催化剂Fe3O4-ZIF-8@ET 2.0。以酶比活力和蛋白负载率为指标，以固定化时间、加酶量及固定化温度为考察因素，对Fe3O4-ZIF-8@ET 2.0的制备工艺进行了单因素实验优化。通过扫描电子显微镜、透射电子显微镜和傅里叶红外光谱仪对复合固定化酶的微观形貌和官能团进行表征。将Fe3O4-ZIF-8@ET 2.0用于催化米糠油脱臭馏出物的酯化反应，考察其催化性能和重复使用性。结果表明：Fe3O4-ZIF-8@ET 2.0制备的最佳工艺条件为固定化时间6 h、加酶量1.5 mL（六水合硝酸锌 0.225 g，2-甲基咪唑0.622 g，磁性纳米粒子Fe3O4 0.05 g）、固定化温度40 ℃，在此条件下Fe3O4-ZIF-8@ET 2.0的酶比活力为50.58 U/g，蛋白负载率为86.64%；表征结果表明Eversa Transform 2.0被成功负载到Fe3O4-ZIF-8上；采用Fe3O4-ZIF-8@ET 2.0催化米糠油脱臭馏出物酯化，酯化率达到94.4%，重复使用5次后，相对酶活力达到57.37%。综上，制备的复合纳米生物催化剂Fe3O4-ZIF-8@ET 2.0具有良好的催化性能，表现出较大的工业化应用潜力。 In order to improve the stability and utilization of liquid lipase Eversa Transform 2.0, the magnetic nanoparticles Fe3O4 were coupled to the metal-organic framework material ZIF-8 by the co-precipitation method, and Eversa Transform 2.0 was loaded on the composite material to prepare the composite nano-biocatalyst Fe3O4-ZIF-8@ET 2.0. With enzyme specific activity and protein loading rate as indicators, and immobilization time, enzyme dosage, and immobilization temperature were as factors, and the preparation process for Fe3O4-ZIF-8@ET 2.0 was optimized by single factor experiment. The microscopic morphology and functional groups of the composite immobilized enzyme were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier infrared spectroscopy (FT-IR). The Fe3O4-ZIF-8@ET 2.0 was used to catalyze the esterification reaction of rice bran oil deodorized distillate, and its catalytic performance and reusability were investigated. The results showed that the optimal conditions for preparing Fe3O4-ZIF-8@ET 2.0 were obtained as follows: immobilization time 6 h, enzyme dosage 1.5 mL(zinc nitrate hexahydrate 0.225 g, 2-methylimidazole 0.622 g, and Fe3O4 nanoparticles 0.05 g), and immobilization temperature 40 ℃. Under these conditions, the specific activity of Fe3O4-ZIF-8@ET 2.0 was 50.58 U/g, and the protein loading rate was 86.64%. The characterization results indicated that Eversa Transform 2.0 was successfully loaded onto Fe3O4-ZIF-8. With Fe3O4-ZIF-8@ET 2.0 as catalyst, the esterification rate of rice bran oil deodorized distillate was 94.4%, and after five batches, the relative enzyme activity of the immobilized enzyme could still reach 57.37%. In conclusion, the composite nano-biocatalysts Fe3O4-ZIF-8@ET 2.0 has good catalytic performance, and shows great potential for industrial application.